Exposure to nanoplastics and nanomaterials either single and combined affects the gill-associated microbiome of the Antarctic soft-shelled clam Laternula elliptica - Rodolfo Rondon; Céline Cosseau; Elisa Bergami; César A. Cárdenas; Carolina Pérez-Toledo; Diego Alvarez; Jacqueline Aldridge; Alejandro Font; Ignacio Garrido; Francisco Santa Cruz; Garance Perrois; Teresa Balbi; et al. (Marine Environmental Research, 2024)

Environmental impact on marginal coastal benthic communities within the Jeju Island, South Korea temperate transition zone - Garance Perrois; Anna B. Jöst; Kyeong-Tae Lee; Leonard M. T. Pons; Hyun-Sung Yang; Young Baek Son; Heung-Sik Park; Do-Hyung Kang; Taihun Kim (Frontiers in Marine Science, 2024)
Aim of study Marine climatic transition zones are boundary areas of major climate zones, here the boundary between the subtropical and temperate zones. They present areas containing high abundance of organisms living at the limit of their physiological tolerance. These marginal populations are particularly sensitive to changes in their environment. As such, marine climatic transition zones are excellent natural playgrounds for climate change-related hypothesis testing, especially with respect to marine habitat response to ocean warming. The marginal biogenic habitats around Jeju Island, South Korea, which lies within the temperate transition zone, have gradually changed from macroalgal-dominated to hard coral-dominated habitats. Understanding the specific abiotic environmental factors that influence the distribution of the marginal populations in temperate transition zones (i.e., species at their occurrence limit) is crucial to predicting and managing temperate zone habitat changes caused by climate change. This study aims to identify the specific abiotic environmental factors that contribute to explaining the current spatial distribution of the declining temperate and expanding subtropical foundation species in Jeju waters. Methods Coverage and composition of sessile benthic communities were determined by photo-quadrat analysis at two depths (10 m and 15 m) at three sites along the island’s south, east, and north coasts in May and November 2022. Divergences in community composition between sites were characterized in light of ten quantitative environmental parameters. Results Our results show that sessile foundation communities vary significantly at different sites around the island. While the south is defined by high-latitude hard corals, predominately Alveopora japonica , the east is defined by the temperate canopy-forming macroalga Ecklonia cava , and the north is characterized by coralline algae. Winter sea surface temperature, water transparency, nutrient concentration, and water movement were statistically the most impactful environmental factors determining which foundation species constitute each distinct benthic community. Conclusion This study provides valuable baseline information on the impacts of abiotic environmental factors on marine sessile communities in a temperate transition zone.

Correction: Microbiome profile of the Antarctic clam Laternula elliptica - Marcelo González-Aravena; Garance Perrois; Alejandro Font; César A. Cárdenas; Rodolfo Rondon (Brazilian Journal of Microbiology, 2024)

Microbiome profile of the Antarctic clam Laternula elliptica - Marcelo González-Aravena; Garance Perrois; Alejandro Font; César A. Cárdenas; Rodolfo Rondon (Brazilian Journal of Microbiology, 2024)

Monitoring ecological dynamics on complex hydrothermal structures: A novel photogrammetry approach reveals fine‐scale variability of vent assemblages - Loïc Van Audenhaege; Jozée Sarrazin; Pierre Legendre; Garance Perrois; Mathilde Cannat; Aurélien Arnaubec; Marjolaine Matabos (Limnology and Oceanography, 2024)
We set out to characterize the fine‐scale processes acting on interannual dynamics of deep‐sea vent fauna by using a novel approach involving a 5‐yr time series of 3D photogrammetry models acquired at the Eiffel Tower sulfide edifice (Lucky Strike vent field, Mid‐Atlantic Ridge). Consistently, with the overall stability of the vent edifice, total mussel cover did not undergo drastic changes, suggesting that they have been at a climax stage for at least 25 yr based on previous data. Successional patterns showed consistency over time, illustrating the dynamic equilibrium of the ecological system. In contrast, microbial mats significantly declined, possibly due to magmatic events. The remaining environmental variability consisted of decimeter‐scale displacement of vent outflows, resulting from their opening or closure or from the progressive accretion of sulfide material. As a result, vent mussels showed submeter variability in the immediate vicinity of vent exits, possibly by repositioning in response to that fine‐scale regime of change. As former studies were not able to quantify processes at submeter scales in complex settings, this pioneering work demonstrates the potential of 3D photogrammetry models for conducting long‐term monitoring in the deep sea. We observed that the ability of mussels to displace may enable them to cope with changing local conditions in a stable system. However, the long‐term stability of mussel assemblages questions their capacity to withstand large‐scale disturbances and may imply a low resilience of these “climax” communities. This suggests that they may be particularly vulnerable to the negative effects of mining activities in hydrothermal ecosystems.

Impact of Super Typhoon ‘Hinnamnor’ on Density of Kelp Forest and Associated Benthic Communities in Jeju Island, Republic of Korea - Kyeong-Tae Lee; Garance Perrois; Hyun-Sung Yang; Taeho Kim; Sun Kyeong Choi; Do-Hyung Kang; Taihun Kim (Journal of Marine Science and Engineering, 2023)
This study was carried out to determine the levels of resistance and resilience of kelp forests to large-scale physical disturbances. Our study site, Seongsan, Jeju Island, was impacted by super typhoon ‘Hinnamnor’. Before the typhoon, Seongsan had shown high ecosystem stability. Our results indicated that the ecological stability of a kelp forest facing a severe typhoon is strongly linked to the prevailing environmental conditions. Although typhoon impact resulted in a significant loss of brown macroalgae canopy, Ecklonia cava remained dominant within the kelp forest community. Resistance and resilience levels strongly depended on water temperature and movement and presence of turf-forming algae. Hence, hydrodynamic and biological factors strongly influence the overall stability of a kelp forest. We also report the first occurrences of a scleractinian coral species (i.e., Montipora millepora) at Seongsan, which became visible after canopy loss following the typhoon. Our findings provide valuable ecological information about the benthic community of kelp-dominated ecosystems and are essential to mitigate the impacts of expected climate change-driven rises in seawater temperature and the frequency of super typhoons.